Reconstructed Late Summer Maximum Temperatures for the Southeastern United States From Tree‐Ring Blue Intensity - Karen E. King; Grant L. Harley; Justin T. Maxwell; Shelly Rayback; Edward Cook; R. Stockton Maxwell; Maegen L. Rochner; Ellen V. Bergan; Zachary Foley; Matthew Therrell; Joshua Bregy (Geophysical Research Letters)
Abstract Over recent decades, the southeastern United States (Southeast) has become increasingly well represented by the terrestrial climate proxy record. However, while the paleo proxy records capture the region's hydroclimatic history over the last several centuries, the understanding of near surface air temperature variability is confined to the comparatively shorter observational period (1895‐present). Here, we detail the application of blue intensity (BI) methods on a network of tree‐ring collections and examine their utility for producing robust paleotemperature estimates. Results indicate that maximum latewood BI (LWBI) chronologies exhibit positive and temporally stable correlations (r = 0.28–0.54, p < 0.01) with summer maximum temperatures. As such, we use a network of LWBI chronologies to reconstruct August‐September average maximum temperatures for the Southeast spanning the period 1760–2010 CE. Our work demonstrates the utility of applying novel dendrochronological techniques to improve the understanding of the multi‐centennial temperature history of the Southeast.